Timing of anticoagulation therapy in patients with acute ischaemic stroke and atrial fibrillation - Paciaroni, Maurizio; Agnelli, Giancarlo; Ageno, Walter; Caso, Valeria (Thrombosis and Haemostasis, 2016)
In patients with acute stroke and atrial fibrillation (AF), the risk of early recurrence has been reported to range between 0.1% and 1.3% per day. Anticoagulants are the most effective therapy for the prevention of recurrent ischaemic stroke in these patients, but randomised clinical trials have failed to produce any evidence supporting the administration of heparin within 48 hours from stroke onset as it has been associated with a non-significant reduction in the recurrence of ischaemic stroke, no substantial reduction in death and disability, and an increase in intracranial bleeding. As early haemorrhagic transformation is a major concern in the acute phase of stroke patients with AF, determining the optimal time to start anticoagulant therapy is essential. This review which focuses on the epidemiology of recurrent ischaemic stroke and haemorrhagic transformation in patients with acute ischaemic stroke and AF, proposes a model for decision making on optimal timing for initiating anticoagulation, based on currently available evidence.
Keywords: Atrial fibrillation; ischaemic stroke; secondary prevention; acute therapy